PERSEPSI INSAN PERPUSTAKAAN TERHADAP FUNGSI PERPUSTAKAAN NASIONAL BERKAITAN PERATURAN PERUNDANG-UNDANGAN - Subagyo Subagyo (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
This study was held in October 2017 in the National library of Indonesia to stakeholders who had been invited to certain discussion meetings. The purposive random sampling technique by accidental sampling was applied in this study. The study aimed to determine the library user’s perception to the function of the National Library of Indonesia related to legistation. According to Law No.43/2007, the functions of the National Library are as the builder, referral, deposit, research, conversation, and network center library. The study sugessted that the respondent’s perception on the function of library as the bulider library becomes the most prominent item of its authority; while the function of library as the research library becomes the lowest item.